You are on page 1of 4

# Excel Review Center Solution to Take Home Exam – Algebra 1

## Question 1 CALCULATOR: Answer: x = 3

Input the equation then use the CALC
A. the final digit whether zero or not zero function. Let x = 1: Problem 14
5x x+3 2x + 1
Question 2 − +
2x 2 + 7x + 3 2x 2 − 3x − 2 x 2 + x − 6 4 3 1 6
+ = −
5 (1) 1+ 3 2 (1) + 1 x −1 x +1 2x x 2 − 1
C. leading digit − + 2
2 2 4x + 4 + 3x − 3 x 2 − 1 − 12x
2 (1) + 7 (1) + 3 2 (1) − 3 (1) − 2 (1) + (1) − 6 =
Question 3 x2 − 1 (
2x x 2 − 1 )
=1
D. 5 Then from the choices, 2 2
8x + 8x + 6x − 6x = x − 1 − 12x 2

Let x = 1:
4 4 13x 2 + 14x + 1 = 0
Question 4 →
D. 7 x+3 1+3 1
x=− , x = −1
1 → satisfies the given equation 13
Question 5
Problem 11 CALCULATOR:
A. 3 Input the equation then use the SHIFT CALC
n −1 2n −1 function:
Question 6 ( xy ) ( a − b ) ( a − b ) Answer: x = -1/13 or x = -1
 xy ( a − b )2  n −1
B. 0.01414   Problem 15
n 2n − 2

Question 7 ( xy ) ( a − b )
= n −1 2n − 2
= xy (
x 4 + 5x 2 − 36 = x 2 + 9 x 2 − 4 )( )
( xy ) ( a − b )
C. evolution = (x 2
+ 9 ) ( x − 2 )( x + 2 )

Question 8 CALCULATOR:
Assume values for variables a,b, x and y, Problem 16
D. involution then use the CALC function.(Same with the
previous problem.) x3 + 3x 2 − 4x − 12 = x 2 ( x + 3 ) − 4 ( x + 3 )
Problem 9
Problem 12 = ( x + 3 ) x2 − 4 ( )
x + 1 2x = ( x + 3 )( x − 2 )( x + 2 )
+ = 47 − 2x
3 4 a2 − b2 a2 a − 2b
⋅ 2 ⋅
4x + 4 + 6x ab a − ab − 2b2 a − b Problem 17
= 47 − 2x
12 ( a − b )( a + b ) ( a2 ) ( a − 2b ) a
= =
4x + 4 + 6x = 564 − 24x ( ab )( a − 2b )( a + b )( a − b ) b ( )(
81 − x 4 = 9 + x 2 9 − x 2 )
4x + 6x + 24x = 564 − 4
= ( 9 + x ) ( 3 − x )( 3 + x )
2

## 34x = 560 CALCULATOR: (Same with the previous

x = 16.47 problem)
Input the equation then use the CALC Problem 18
CALCULATOR:
Input the equation then use the SHIFT CALC function. Let a=1, b=2:
3x + y 2y 1
function: a2 − b2 a2 a − 2b − −
⋅ 2 ⋅ x2 − y2 x ( x − y ) x + y
ab a − ab − 2b2 a − b
2 2
(1) − ( 2 ) ⋅ (1)
2
(1) − 2 ( 2 ) =
( 3x + y ) x − 2y ( x + y ) − x ( x − y )
Problem 10 = ⋅
2 2 x ( x − y )( x + y )
( )( ) (1) − (1)( 2 ) − 2 ( 2) (1) − ( 2 )
1 2
5x x+3 2x + 1 1 3x 2 + xy − 2xy − 2y 2 − x 2 + xy
− + = =
2x + 7x + 3 2x 2 − 3x − 2 x 2 + x − 6
2
2 x ( x − y )( x + y )
5x x+3 2x+1 Then from the choices,
= - +
(2x+1)(x+3) (2x+1)(x-2) (x-2)(x+3) Let a = 1, b= 2: =
2x 2 − 2y 2
=
(
2 x2 − y2
=
2 )
2 2 a 1 x ( x − y )( x + y ) x x 2 − y 2
( x )
5x ( x − 2 ) − ( x + 3 ) + ( 2x + 1) = → satisfies the given equation
= b 2
( 2x + 1)( x + 3 )( x − 2 ) Problem 19
5x 2 − 10x − x 2 − 6x − 9 + 4x 2 + 4x + 1 Problem 13
= 2 2
( 2x + 1)( x + 3 )( x − 2 ) 2x 3 ( x − 1) − ( x − 2 )
= x −1 x − 2
x2 + x − 2 x + 2 − ( x − 2 )( x − 1)
8x 2 − 12x − 8 x − 2 x −1 =
= 2x 3
( 2x + 1)( x + 3 )( x − 2 ) = 1

1 ( x − 2 ) − ( x − 1)
( x + 2 )( x − 1) x + 2 x −1 x − 2
4 ( 2x + 1)( x − 2 ) ( x − 2 )( x − 1)
= 2x = 3x − 3
( 2x + 1)( x + 3 )( x − 2 )  x − 1 2 − x − 2 2   ( x − 2 )( x − 1) 
x=3
=
( ) ( )  
=
4  ( x − 2 )( x − 1)   ( x − 2 ) − ( x − 1) 
x+3 CALCULATOR:   
Input the equation then use the SHIFT CALC
function:
Excel Review Center Solution to Take Home Exam – Algebra 1
2 2

=
( x − 1) − ( x − 2 ) =
2
x − 2x + 1 − x + 4x − 42
Problem 26 Problem 34
( x − 2 ) − ( x − 1) −1
= 3 − 2x 15 = 1× 15 a x c −2 x = b3 x +1
28 = 1× 2 × 2 × 7 ax c −2 xb−3 x = b
Problem 20
∴ Greatest common divisor is 1 log ( ax c −2 xb−3 x ) = logb
5x3 y −1 1 xy3 logax + logc −2 x + logb−3 x = logb
= x3 − 2 y ( ) = Problem 27
−1− −4
2 −4
15x y 3 3 xloga − 2 xlogc − 3xlogb = logb
12 = 3 × 4 logb
Problem 21 16 = 4 × 4 x=
loga − 2 logc − 3 logb
3
∴ Greatest common divisor is 4
3
3
16x11y 2 = 3 2 ( 2 ) x 3 ( ) x 2 y 2 = 2x 3 3 2x 2 y 2 Problem 35
Question 28
Problem 22 2log ( 3 − x ) = log2 + log ( 22 − 2x )
A. imaginary
2
2x + 1 x + 8 log ( 3 − x ) = log2 ( 22 − 2x )
=
x−5 −7x Problem 29 2

−14x − 7x = x 2 + 3x − 40
2 (3 − x ) = 44 − 4x
 3
15x 2 + 10x − 40 = 0 a3  a3 
 = log  5 2 
a
2

4 = log  5 2 
x = 7 x = −5
x = −2,
5 2
cb c b   cb 
    Substitute the values in the given
3
3 equation, x=7 will five log of negative
Problem 23 = loga 2 − logc 5 − logb2 number, and x=-5 will result to a
3 logarithm of a positive value.
= loga − 5logc − 2logb
x + 1 + 2x + 3 − 8x + 1 = 0 2 ∴ Answer is x = −5
2
( x +1 = ) ( 8x + 1 − 2x + 3 ) Problem 30
Problem 36
x + 1 = ( 8x + 1) − 2 ( 8x + 1)( 2x + 3 ) + ( 2x + 3 ) log10 3 = 0.4771
6
2
log10 4 = 0.6021 log2x 3 + log = 6.278
( x+1-8x-1-2x-3 ) = -2 ( 8x+1)( 2x+3 ) 
2
x
2
(
log10 12 = log10 ( 3 )( 4 ) ) log12x 2 = 6.278
 
 −3 ( 3x + 1)  = 4 ( 8x + 1)( 2x + 3 ) log10 12 = log10 3 + log10 4 12x 2 = 106.278
( )
9 9x 2 + 6x + 1 = 4 16x 2 + 26x + 3 ( ) log10 12 = 1.0792 x = 397.56
2 2
81x + 54x + 9 = 64x + 104x + 12 Problem 37
Problem 31
17x 2 − 50x − 3 = 0
1 log4 7 = n log2 2 + log2 x = 2
x = 3, x = − → discarded
17 1 log2 2x = 2
log4 = log4 7 −1
Substitute the two values in the 7 2x = 4
equation given, the value that will − log4 7 = −n x=2
satisfy the equation
Problem 32 Problem 38
is x = 3.

## Problem 24 log3 ( x 2 - 8x ) = 2 x 3 log x = 100x

x 2 − 8x = 9 3logx(logx) = log(100x)
The LCM is the product of the highest power 3logx(logx) = log100 + logx
of each prime factor of the given numbers (x − 9)(x + 1) = 0
26 = 13 × 2 x = 9 l x = −1 3(logx)2 − logx − 2 = 0
39 = 13 × 3 Let y = logx
66 = 11× 3 × 2 Problem 33 3(logx)2 − logx − 2 = 0
∴ least common multiple is: 3y2 − y − 2 = 0
logb y = 2x + logb x
=13 × 2 × 3 × 11 = 858 y = 1,y = −2 / 3(absurd)
logb y − logb x = 2x
When,logx = 1
Problem 25 y
logb = 2x x = 10
x
12 = 22 × 3 y
= b2x Problem 39
18 = 32 × 2 x
y = xb2x log4 ( log3 5 ) = 0.275 → (use calculator)
21 = 3 × 7
2
25 = 5
Problem 40
35 = 3 × 7
lne xy = xy
∴ LCM is: = 22 × 32 × 7 × 52 = 6300
Excel Review Center Solution to Take Home Exam – Algebra 1
Problem 54
Problem 41 Problem 48
Solving for the roots of the given equation by
log3 4x + log3 x = log3 144 Remainder,R: Q.F.:
log3 ( 4x × x ) = log3 144 R = f(1 3) x = 5 / 2 l x = −1
4 3 2 Taking the reciprocal, x1 ' = 2 5 l x 2 ' = −1
2
4x = 144 R = 3 (1 3 ) + 5 (1 3 ) − 5 (1 3 ) + 10 (1 3 ) − 1
Thus, the required equation is:
x 2 = 36 R=2
2
x = −6 → discarded (x − )(x + 1 = 0
Problem 49 5
x = 6 → Answer 2x 2
x2 + x − − =0
Using Quadratic Formula: x = −1 ± 2i 5 5
Problem 42
5x 2 + 5x − 2x − 2 = 0
Problem 50
log5 4x + log5 x = log5 100 5x 2 + 3x − 2 = 0
log3 ( 4x × x ) = log3 100 Remainder,R:
Problem 55
2
4x = 100 R = f( −5)
6 5 4 2
x 2 = 25 R = ( -5 ) +7 ( -5 ) +10 ( -5 ) - ( -5 ) - ( -5 ) 1 2
(x − )(x + ) = 0
x=5 2 3
R=0
2x x 1
x2 + − − =0
Question 43 3 2 3
Problem 51
x 1
Remainder,R: x2 + − = 0
D. positive value or zero 6 3
f(2) = 16
6x 2 + x − 2 = 0
Problem 44 (2)
4 3 2
+ a ( 2 ) + 5 ( 2 ) + b(2) + 6 = 16
16 + 8a + 20 + 2b + 6 = 16 Problem 56
From sum of roots formula:
b  −10  8a + 2b + 26 = 0
Sum = − = −  Solving for the roots of the given equation by
=2 4a + b + 13 = 0 →
a  5  Q.F., we get
When divided by x+1:
−b ± b2 − 4ac
Remainder,R: x=
Problem 45 2a
f( −1) = 10
2 2 4 3 2 −7 ± 72 − 4 (1)( −2 )
a x + 4c x − 10c = 5a − 4acx ( −1) + a ( −1) + 5 ( −1) + b( −1) + 6 = 10 x=
2(1)
a2 x + 4c 2 x + 4acx = 5a + 10c 1 − a + 5 − b + 6 = 10
−7 + 57 −7 − 57
x(a2 + 4c 2 + 4ac) = 5a + 10c a + b − 2 = 0 → x= l x=
Solving the two equations simultaneously: 2 2
5(a + 2c) The new roots are:
x= 4a + b + 13 = 0 →
(a2 + 4c 2 + 4ac) 7 − 57 7 + 57
a + b − 2 = 0 → x= l x=
5(a + 2c) 2 2
x= We get, a = -5 and b = 7.
(a + 2c)(a + 2c) Thus, the required equation is:
5 x 2 − 7x − 2 = 0
x=
(a + 2c) Problem 52
Problem 57
Problem 46 Solving for f(k)=k.
(k + 3)(k − 4) + 4 = k Let,
12 12 2 x1 be one of the root.
( 5x − 4 ) = ( 2x + 1) +1 k − 4k + 3k − 12 + 4 = k
2x1 be the other root
5x − 4 = ( 2x + 1) + 2 2x + 1 + 1 k 2 − 2k − 8 = 0 Then, from sum of roots formula:
(k − 4)(k + 2) = 0 x1 + 2x1 = − ( −k )
5x − 2x − 4 − 2 = 2 2x + 1
k = 4 l k = −2 3x1 = k →
3x − 6 = 2 2x + 1
Also, from product of roots formula:
9x 2 − 36x + 36 = 4 ( 2x + 1) Problem 53 x1 ( 2x )1 = 18
9x 2 − 44x + 32 = 0 2
Using long division: 2 ( x1 ) = 18
x=4 3x 2 + 6x + 8 2

8
( x1 ) =9
x = → discarded x 3 − 2x 2 + 6 3x5 + 0x 4 − 4x 3 + 2x 2 + 36x + 48
9 x1 = ±3
3x5 − 6x 4 + 0x 3 + 18x 2
Substituting the two values in Thus solving for k from equation 1 we get k =
0 + 6x 4 − 4x 3 − 16x 2 + 36x 3x1 = 3(±3)
the given equation, only x = 4
0 + 6x 4 − 12x 3 + 0x 2 + 36x k = ±9
will satisfy the equation.
8x 3 − 16x 2 + 48 Problem 58
Problem 47 8x 3 − 16x 2 + 48
Remainder,R: 0 Express the given in general form:
2 3 4x2 − 8x + 5 = 0
R = f(4 3) = 6(4 3) − 30 + 9 ( 4 3 ) = 2
By inspection, we get:
Excel Review Center Solution to Take Home Exam – Algebra 1
A = 4, B = -8, and C = 5 1
Solving for discriminant: y1 = l y 2 = −3 Problem 71
2
D = B2 − 4AC Solving for x:
2 From the formula:
D = ( −8 ) − 4 ( 4 )( 5 ) 1
x1 5 = , x1 5 = −3 4th term = nCr −1xn − r +1yr −1
D = −16 2
7 − 4 +1 4 −1
1 4th term = 7C4 −1 ( a ) ( −2x )
x= , x = −243
Problem 59 32 = 35a4 ( 8x3 )

## Using the discriminant, one real solution: Problem 65 = −280a4 x3

D = B2 − 4AC = 0 Problem 72
If the roots are equal, the discriminant
D = k 2 − 4 ( 4 )(1) = 0 must be zero:
D = (2k + 4)2 − 4(9k) = 0 From the formula:
k 2 = 16
2
4k + 16k + 16 − 36k = 0 5th term = nCr −1x n − r +1yr −1
k=4
8 − 5 +1 5 −1
4k 2 − 20k + 16 = 0 5th term = 8C5 −1 ( 3y ) ( −4w )
Problem 60 4 5 −1
k = 1, k = 4 = 70 ( 3y ) ( −4w )
Substitute x = 3 to the given equation. = 1,451,520y 4 w 4
3 2
( 3 ) − 2 ( 3 ) − 3k = 0 Problem 66
k =3 Problem 73
(x + y)log5 = 2 From the formula:
Problem 61 2 yrth term = nCr x n −r yr
x+y= →
log5 5
From sum of roots formula: y 5 = 10C5 ( 2x 2 ) y5
(2x − y)log2 = 1
 −k  = 8064x10 y5
x1 + x 2 = −   1
 2  2x − y = →
log2
k
x1 + x 2 = → Problem 74
From the given that the difference 2 1 From the formula:
3x = + r th term = nCr −1xn − r +1yr −1
between roots is 5/2. log5 log2
5 = ( 2x 2 )
9 − r +1 r −1
x1 − x 2 = → x = 2.06 (x )
−1

2
From product of roots formula: Collect variables:
Problem 67 9 − r +1 r −1
3k
( x1 )( x2 ) = → 2
(x )
2
(x )
−1
= x0
2 Let y = x
Manipulating the 3 equations: x 20 − 2r x1− r = x 0
y 2 − 10y + 9 = 0
k = - 1, k = 25 x 21− 3r = x 0
y = 1,y = 9
But, y =x2 21 − 3r = 0
Problem 62 x 2 = 1, x2 = 9 r =7
If one root is the reciprocal of the other, then x = ±1, x = ±3 Solving for the coefficient of the 7th term:
the product of the roots must be 1. 1
7th term = 9C7 −1(2x 2 )9 − 7 +1( )r −1
C Problem 68 x
=1
A = 9C6 2 3
( )
5k  7
=1 ( x − 2)( x + 3 )  x − 5  = 672
2  
2 = 5x 3 − 2x 2 − 37x + 42 = 0 Problem 75
k=
5 From the formula:
Problem 69
Problem 63 6th term = nCr −1x n − r +1yr −1
16 − 6 + 1
Using discriminant: x + 3y + 4z = 15  1  5
6th term = 16C6 −1   ( −3 )
D = (B)2 − 4AC −2x + 4y + 5z = 12  2a 
2
D = ( −12 ) − 4 ( 4 )( 9 ) 3x + y + 6z = 29  1 
= 4368  11 
( −243)
D=0 Using calculator, we get: x=2  2048a 
66339
Since the discriminant is zero, the roots =−
Problem 70 128a11
are “rational and equal”.
x + 2y − z = 10
Problem 64 2x − y + 2z = −3
Let y = x1/5 3x + 2y + 3z = 6
2y 2 + 5y − 3 = 0 Using calculator, we get: x=2
Solving for y using Q.F., we get: